Problematika Penggunaan Aplikasi Google Classroom dalam Meningkatkan Motivasi Belajar PAI dan BP pada Masa Pandemi Covid-19 di SMAN 1 Teluk Kuantan - Sopiatun Nahwiyah S.Pd.I., MA; Bustanur Bustanur; Zulhaini Zulhaini; Ikrima Mailani; Elena Doxic (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2022)
Covid-19 which emerged in March 2020 has given birth to various policies in education, one of which is the implementation of education not only face-to-face but also through Learning from Home (BDR). Google Classroom is an application that can access online learning like being in a classroom. Teachers of Islamic Education and Budi Pekerti at SMAN 1 Teluk Kuantan also use the Google Classroom application to support PAI and BK learning. Based on the observations of Islamic Education and Budi Pekerti learning and based on interviews the learning implementation process using Google Classroom there are several problems. The purpose of this study was to find out the problems of using the Google Classroom application in increasing motivation to learn Islamic Religious Education and Morals during the covid-19 pandemic at SMAN 1 Teluk Kuantan. Qualitative research methods, with data collection techniques are observation, questionnaires, interviews and documentation. And data analysis techniques using data triangulation, namely data reduction, data presentation and conclusions. The results of the study are the Problems of Using Google Classroom Applications in Increasing PAI and BP Learning Motivation during the Covid-19 Pandemic at SMAN 1 Teluk Kuantan Tp. 2020/2021 are: Constraints from Students, Constraints from Teachers, Constraints from Parents, Internet Quota Constraints, Network Constraints.